APPROACHES TO THE MANAGEMENT OF OPERATING CASH FLOWS ON THE BASIS OF THE IMPLEMENTATION OF THE STRATEGY OF THE COMPANY MARKET VALUE GROWTH - Yakymova, A. M. (Science and Transport Progress, 2005)
The article offers approaches to management of operating money flows of the enterprise on the basis of realization of the strategy of increased market value of the enterprise, which requires usage of efficient methods of evaluating the management of operating money flows. The task of the estimation of operational money flows management has been formulated with account of the profitability concept and that of the risk of economic operations.